Pengaruh Profitabilitas, Ukuran Perusahaan, Dan Likuiditas Terhadap Nilai Perusahaan Pada Perusahaan Sektor Industri Dasar Dan Kimia Yang Terdaftar Di Bursa Efek Indonesia - Yanti Erlina, Maria; Mursalin, Adi (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2024)
This research aims to determine whether or not there is an influence of profitability, company size and liquidity on company value in basic industrial and chemical sector companies listed on the Indonesia Stock Exchange from 2018 to 2022. The form of research used in this research is quantitative research. . The sampling method used was the purposive sampling method. Data analysis in this study used the statistical product and service solution (SPSS) version 22 program. Data analysis used in this study consisted of descriptive statistics, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression analysis, coefficient of determination test , F test (simultaneous)), and T test (partial).